STRUCTURAL-SEMANTIC ANALYSES OF THE PHRASEME TRANSLATION IN “BABURNAME” - Mukhammadiyeva Dilafruz Akhtamovna (Galaxy International Interdisciplinary Research Journal, 2021)
Phrasemes changed to their equivalents. As phraseologisms are translated, it is definite that full equivalents cannot be found to all of them. That is why, in translating the phraseologism that has no full equivalent the translator should use another method. In the process of translation, the material of one language is constituted by another, so all the literary means are recreated again by the translator in his native language. The aim translating is to obtain, preserve and pass the original version(information), but not to create a new work that has no prototype, the aim of translating is to recreate.